Folate receptor-targeted mixed polysialic acid micelles for combating rheumatoid arthritis: in vitro and in vivo evaluation. (1st January 2018) - Zhang, Nan; Xu, Chunyu; Li, Na; Zhang, Shasha; Fu, Lingling; Chu, Xiao; Hua, Haiying; Zeng, Xianghui; Zhao, Yongxing
Abstract: Objective: Rheumatoid arthritis (RA) is associated with chronic inflammation. The suppression of inflammation is key to the treatment of RA. Glucocorticoids (GCs) are classical anti-inflammatory drugs with several disadvantages such as poor water solubility and low specificity in the body. These disadvantages are the reasons for the quick elimination and side effects of GCs in vivo . Micelles are ideal carriers for GCs delivery to inflamed synovium. We set out to improve the targeting and pharmacokinetic profiles of GCs by preparing a targeting micelle system. Methods: In this study, natural chlosterol (CC) and folic acid (FA) were used to fabricate polysialic acid (PSA) micelles for the targeted delivery of Dexamethasone (Dex). The biodistribution and therapeutic efficacy of the resulting micelles were evaluated in vitro and in vivo . Results: PSA-CC and FA-PSA-CC micelles showed a size below 100 nm and a moderate negative charge. PSA-CC and FA-PSA-CC micelles could also enhance the intracellular uptake of Dex and the suppression of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in vitro and in vivo . Arthritis mice showed reduced paw thickness and clinical arthritis index using PSA-CC and FA-PSA-CC micelle treatment. Micellized Dex demonstrated a 4 ∼ 5 fold longer elimination half-life and a 2 ∼ 3 folds higher bioavailability than commercial Dex injection. FA modification significantly improved the anti-inflammatory efficacy of PSA-CC micelles. Conclusion: FA-PSA-CC micelles demonstrated significant advantages in terms of the suppression of inflammation and the treatment of inflammatory arthritis. These reliable and stable micelles possess a high potential to be transferred for clinical use.